2012
DOI: 10.1007/s10236-012-0580-2
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for producing refined currents in the Equatorial Atlantic in the context of the search of the AF447 wreckage

Abstract: On the night of 1st June 2009, a Rio-Paris Air France flight (AF447) disappeared in a highly variable and poorly observed part of the western tropical Atlantic Ocean. The first debris was located 5 days after the accident. Several reverse drift computations were conducted in order to define the likely position of the wreckage. Unfortunately, the performance of the operational ocean analyses available in the region of interest ranges from 80 to 100 km of positioning error after 5 days of inverse drift computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The airplane disappeared on June 1st 2009 near 3 • N and 31 • W, and a large international effort was organized to try to find the wreckage. The contribution of oceanographers is described in (Ollitrault 2010) and part of it in Drévillon et al (2012). This region is very challenging for ocean models because of tropical waves and especially for SURCOUF because of the breakdown in geostrophic balance at the equator.…”
Section: Study Regionmentioning
confidence: 99%
“…The airplane disappeared on June 1st 2009 near 3 • N and 31 • W, and a large international effort was organized to try to find the wreckage. The contribution of oceanographers is described in (Ollitrault 2010) and part of it in Drévillon et al (2012). This region is very challenging for ocean models because of tropical waves and especially for SURCOUF because of the breakdown in geostrophic balance at the equator.…”
Section: Study Regionmentioning
confidence: 99%
“…The corresponding probability of other area r is updated to 1 ' 1 r r r pq = > − (There is in a similar way) As for after search some primary simulating point (1,1), calculate primary joint probability p0 is 0.2883. After search, the probability of this point is updated to:…”
Section: Establish Bayesian Net and Combine Every Factor To Constructmentioning
confidence: 99%
“…An improved process for taking into account available observations in the assimilation scheme will also be developed thanks to a tuning of the observation errors based on Desroziers criteria (Desroziers et al 2005) and with an optimization of the assimilation window to improve the initial state and consequently the forecast. Previous studies have shown improvements in forecasting with a shorter assimilation window from 7 to 5 days, for example (Drévillon et al 2013), or with a time window depending on the type of observation . From a more long-term perspective, the horizontal and vertical resolution will be improved, and the assimilation scheme will be updated to take into account satellite ocean colour observations, which are already available in real time with a good global coverage and a high resolution.…”
Section: Mercator-ocean (France)mentioning
confidence: 99%
“…The IBI system was developed in 2011 in the context of the EU-founded project MyOcean in collaboration with Puertos del Estado (Spain). This system is characterized not only by the inclusion of the tidal signal in the OGCM (NEMO) model but also by an improved mixed layer scheme (Dombrowsky et al 2012).…”
Section: Regional Systemsmentioning
confidence: 99%